Pattern of Surgical Diseases Affecting Females in a Teaching Hospital in Central India: A Demographic Study - Shehtaj Khan; Vishal Bansal; Sakshi Goyal (The Surgery Journal, 2023)
Introduction Despite progress in eliminating the social and health disparity between men and women during the last century, gender equality remains an elusive goal, particularly in the developing world. This gender-based bias has been found to directly result into poor health outcome in females. Hence, it is vital to know the number and pattern of surgical diseases affecting females in any setup, so as to improve their admission rates and reach out to this neglected half of population. Materials and Methods This was a demographic study done at a teaching hospital in Central India from January to June 2020. Data of patients discharged from female surgery ward were collected from medical record department. Age, diagnosis, urban–rural distribution, and length of hospital stay of patients were noted, and data were analyzed statistically. Results A total of 187 patient records were studied, which revealed that the mean age of the patients was 40.35 years; maximum patients were of gastrointestinal surgery (53.42%) in which the most common diagnosis was cholelithiasis (25.13%). Urological diseases (15.50%), breast diseases (12.83%), perianal disease (9.09%), and thyroid diseases (5.34%) were found in decreasing order of frequency. Overall hospital stays of patients ranged from 1 to 14 days with average stay of 6.35 days. Conclusion In our study, cholelithiasis was found to be the most common surgically treated disease followed by urological diseases. Breast symptoms, although commonly affecting females, did not turn into admissions as there remains a social taboo attached to it. Breast cancer still presents late, despite being the most common cancer in females in India. Approximately 65% patients were discharged within first 5 days of their admission, which indicates good hospital care and improves patient satisfaction levels. Still there is greater need for public health efforts to improve the monitoring, safety, and availability of surgical services to female patients.